Jordan : Technical Assistance Report-Public Investment Management Assessment (PIMA). (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the recommendations given by the IMF mission on improving the public investment management in Jordan. Jordan's public finances have deteriorated since the mid-2000s, resulting in a significant reduction in public investment. In response to several negative external shocks, notably the Iraq and Syria crises and the 2008 global financial crisis, the government has reduced public investment and stepped up the use of public-private partnerships (PPPs). It is recommended to improve the quality of strategic planning by clarifying roles and responsibilities, enhancing coordination mechanisms between the institutions involved, and ensuring that strategic projects go through the Executive Development Plan cycle. The oversight and disclosure practices of PPPs should also be strengthened.